(untitled) (Research, Society and Development, 2022)
Osteoporosis is a condition characterized by deterioration of bone microarchitecture resulting in loss of total bone mass, decreased tissue resistance and increased susceptibility to fractures. The study in question aimed to analyze and debate the risk factors and the effectiveness of forms of prevention related to osteoporosis, given their implication for the general population and the need to disseminate safe and effective forms of behavioral management that can contribute to the decrease in the condition, mainly in the most susceptible individual. For this, 42 articles indexed in Bireme, PubMed, Scielo and UpToDate platforms were selected for discussion of the topic. Thus, it was concluded that the need for active investigation of risk factors by health professionals, as well as the encouragement of preventive practices, especially in the population with higher incidence of the disease.